High-quality accreditation resolutions: An overview of challenges and opportunities for Higher Education Institutions in Colombia - Rincón Moreno, Mauricio; Liloy Valencia, Juliana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The study focused on the texts of high-quality accreditation resolutions of Higher Education Institutions in Colombia. The methodological approach led to a descriptive overview and allowed the construction of qualitative categories that enabled the analysis of the strengths and weaknesses. The results show the gap between the urban and rural contexts; a tendency of official institutions to receive more years of accreditation than private ones and the non-incidence of the academic nature in the number of years of accreditation granted. Improving professors’ working conditions and attending rural areas are some of the priorities that national policies must undertake.